(355) the national income of the U.A.R (Egypt). - Hansen, Bent.; Mead, Donald. (The Institute Of National Planning., 2018)
several estimates of national income in Egypt are available. apart from period 1937- to 1962 . due to differences in definition they are not directly comparable, and at first glance they show rather disparate levels and developments for identical periods